2016
DOI: 10.1038/srep32710
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 8 limits TLR-triggered inflammatory responses through inhibiting TRAF6 polyubiquitination

Abstract: Toll-like receptors (TLRs) have critical roles in innate immunity and inflammation and the detailed mechanisms by which TLR signaling is fine tuned remain unclear. Keratin 8 (CK8) belongs to the type II keratin family and is the major compontent of the intermediate filaments of simple or single-layered epithelia. Here we report that down-regulation of CK8 in mice enhanced TLR-mediated responses, rendering mice more susceptible to lipopolysaccharide (LPS)-induced endotoxin shock and Escherichia coli–caused sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…19 KRT8 plays important roles not only in maintaining cellular structural integrity, but also in various pathological progress, such as insulin resistance, 20 retinal pigment epithelium degeneration, 21 inflammatory responses. 22 Notably, recent studies showed that KRT8 is also involved in tumor progress. KRT8 up-regulation promoted renal cell carcinoma metastasis via IL-11/STAT3 pathway, 23 enhanced migration of gastric cancer cells through TGF-β pathway.…”
Section: Discussionmentioning
confidence: 99%
“…19 KRT8 plays important roles not only in maintaining cellular structural integrity, but also in various pathological progress, such as insulin resistance, 20 retinal pigment epithelium degeneration, 21 inflammatory responses. 22 Notably, recent studies showed that KRT8 is also involved in tumor progress. KRT8 up-regulation promoted renal cell carcinoma metastasis via IL-11/STAT3 pathway, 23 enhanced migration of gastric cancer cells through TGF-β pathway.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that CK8 may be an important signaling molecule regulating the inflammatory response. Our previous study indicated that CK8 prevented the polyubiquitination of TRAF6, thus suppressing NF-κB signaling and TLR-dependent inflammation [ 14 ]. In addition, chronic colitis was found to occur spontaneously in homozygous CK8 −/− FVB/N mice [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic lethality has been reported to occur in about 50% of homozygous CK8 knockout mice. Our previous study demonstrated that CK8 was completely abolished in CK8 −/− mice, while CK8 +/− mice had about half the CK8 level of CK8 +/+ mice in all examined tissues [ 14 ]. Furthermore, CK8 +/− mice were phenotypically similar to wild-type (WT) controls, with only slight crypt proliferation and partial ion transport dysfunction [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, K8 was suggested to be a negative regulator of TLR‐mediated signalling, as it was shown that K8 downregulation in mice leads to increased TLR responses, higher inflammatory cytokine levels and more inflammatory tissue injury in response to lipopolysaccharide‐induced sepsis 31. It is possible that the aggravated diabetes in K8 +/− mice in the present study also, in part, may stem from upregulated inflammatory responses due to increased TLR signalling in the K8‐compromised mice, and this potential association warrants further study.…”
Section: Discussionmentioning
confidence: 99%